ANALISIS PENGARUH JUMLAH PENDUDUK, INFLASI, PERTUMBUHAN EKONOMI, HARGA EMAS, KURS DOLLAR, SBI DAN INDEK GINI TERHADAP IHSG - Heri Sasono (Bajang Institute, 2022)
The purpose of this study was to analyze the effect of macro variables on the Composite Stock Price Index (JCI) for the period 2008 to 2020. The macro variables used were population, inflation, economic growth, gold prices, dollar exchange rate and SBI (7-day reverse). Repo Rate) and Gini Index. The number of years in the sample is 13 years, from 2008 to 2020. Multiple linear regression analysis, T test, F test, coefficient of determination test using SPSS Version 26 software. The conclusion are Inflation and Economic Growth have a significant effect on the JCI and the Population, Gold Price, Dollar Exchange, SBI and Gini Index have no significant effect on the JCI. Then simultaneously Population, Inflation, Economic Growth, Gold Price, Dollar Exchange, SBI and Gini Index have a significant effect on the JCI